The Impact of Brand Leadership and Customer Satisfaction on Customer Loyalty: Evidence from Indonesia - Novitasari, Dewiana; Young, Felina Co; Cahyono, Bambang Tri (IJOSMAS, 2024)
This research aims to determine the influence of brand leadership (consisting of the dimensions of quality, value, innovation, and popularity) felt by consumers of e-commerce sites on customer loyalty through the mediation variable of customer satisfaction among private students. The sample for this research was taken from 1026 private university students in Indonesia using simple random sampling techniques and using SEM (Structural Equation Model) with SmartPLS version 4.0 software as a statistical tool. The results of this research show that all dimensions of brand leadership have a positive and significant effect on customer satisfaction. Likewise, customer satisfaction has a positive effect on customer loyalty. The quality dimension has the greatest influence on encouraging customer satisfaction on e-commerce sites. Then followed by the dimensions of value, innovation, and popularity.